Tinjauan Literatur: Dampak Dualistik Penggunaan ChatGPT terhadap Kemampuan Berpikir Kritis dan Keterampilan Membaca Akademik - Jovan Barracuda Yusa; Yuan Rahmatullah; Slevin Hermansa (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
The rapid integration of ChatGPT into higher education has generated significant debate regarding its dualistic impact on essential academic skills. This literature review aims to critically examine the paradoxical effects of ChatGPT usage on students’ critical thinking abilities and academic reading skills. A systematic literature review method was employed, synthesizing empirical studies, theoretical papers, and systematic reviews published between 2021 and 2026. The analysis of 25 selected articles reveals a pronounced duality: strategic and educational integration of ChatGPT can enhance analytical reasoning, metacognitive monitoring, and critical autonomy by facilitating complex problem-solving and personalized scaffolding. However, uncritical and excessive reliance on the tool leads to cognitive offloading, diminished intrinsic cognitive engagement, and superficial information processing, manifested as "cognitive atrophy" and reduced reading comprehension. The findings indicate that the dual impact is not inherent to the technology itself but is contingent upon usage patterns, educational design, and individual learner characteristics. This review implies that educators must develop structured AI literacy frameworks and collaborative learning models that leverage ChatGPT’s benefits while actively mitigating the risks of cognitive dependency. Future research should focus on longitudinal studies to assess the long-term effects of ChatGPT on cognitive development across diverse disciplines.